الاعلان التجاري المضلل والمسؤولية الجنائية الناجمة عنه (دراسة تحليلية) - Mawloud, Abdulbasit Karim; Akram, Castro Salem (Journal of Legal and Political Studies, 2025)
transparency in advertising have become essential. However, some entities resort to deceptive practices to achieve quick profits, exposing consumers to fraud and undermining fair competition in the market. This highlights the need to combat misleading advertising through strict legal frameworks that hold advertisers criminally accountable when their actions cause material or moral harm. This topic explores the concept of misleading advertising, its effects on consumers and society, and examines the legal aspects and criminal responsibility associated with it. Keywords: Advertising, Misleading, Deception, Fraud, Criminal Liability, Attempt.
Keywords: Keywords Advertising; Misleading; Deception; Fraud; Criminal Liability; Attempt